The tapestry of grace : a novel - Sawyer, Kim Vogel (WaterBrook, 2023)
"A Mennonite widower struggling to raise his mischievous boys becomes the unwilling target of the well-intentioned women's benevolent society in this heartwarming romance inspired by historical events-from the bestselling author of Freedom's Song"--